2015
DOI: 10.1007/s12041-015-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mutations in Mediterranean fever gene, with gender and genotype–phenotype correlations in a Turkish population

Abstract: Familial Mediterranean fever (FMF) is the most common hereditary inflammatory periodic disease, characterized by recurrent episodes of fever, abdominal pain, synovitis and pleurisy. The aim of this study was to determine the frequency and distribution of Mediterranean fever (MEFV) gene mutations and to investigate the clinical characteristics and genotype-phenotype correlation in patients with FMF in Aydin, a province in western Anatolia, Turkey. Therefore, we retrospectively analysed MEFV gene mutations in 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
3
15
0
5
Order By: Relevance
“…During FMF attacks, neurological complications are also reported. In various studies, the prevalence of headache has been reported as approximately 5% to 20% among FMF patients 7,23,25,26. Gedalia et al34 reported that of 101 patients, ten experienced headaches during FMF attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During FMF attacks, neurological complications are also reported. In various studies, the prevalence of headache has been reported as approximately 5% to 20% among FMF patients 7,23,25,26. Gedalia et al34 reported that of 101 patients, ten experienced headaches during FMF attacks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FMF and migraine both have recurrent, periodic, painful symptoms. In the literature, a number of clinical observations have long suggested a possible relationship between headache and FMF 7,2226. Furthermore, a clinical study reported that the prevalence of migraine in patients with FMF was 29.1% in the Turkish population 6.…”
Section: Introductionmentioning
confidence: 99%
“…11 En otro estudio, las mutaciones más comunes observadas en el gen MEFV fueron p.M694V (41,15%), p.E148Q (20,35%), p.M680I(G/C) (12,39%) y p.R761H (9,73%) en la población turca. 12 Las mutaciones en el gen MEFV codifican la proteína pirina, que juega un papel importante en las vías inflamatorias al disminuir la inflamación, especialmente en los neutrófilos; por lo tanto, la proteína mutada puede causar inflamación incontrolable y favorecer la aparición de PSH y de otras variedades de vasculitis. 12 La vasculitis puede ser una manifestación clínica de la FMF con una prevalencia familiar más alta.…”
Section: Introductionunclassified
“…12 Las mutaciones en el gen MEFV codifican la proteína pirina, que juega un papel importante en las vías inflamatorias al disminuir la inflamación, especialmente en los neutrófilos; por lo tanto, la proteína mutada puede causar inflamación incontrolable y favorecer la aparición de PSH y de otras variedades de vasculitis. 12 La vasculitis puede ser una manifestación clínica de la FMF con una prevalencia familiar más alta. En pacientes con FMF, las mutaciones en el gen MEFV pueden actuar como factor de susceptibilidad genética para la vasculitis.…”
Section: Introductionunclassified
See 1 more Smart Citation